THE ROLE OF CITIZENSHIP EDUCATION IN PREVENTING ETHNIC CHINESE BULLYING POST COVID-19 PANDEMIC IN ISLAMIC SCHOOLS - Ervina Halit; Muhammad Turhan Yani; Harmanto (Bajang Institute, 2024)
The aim of this research is to find out and analyze further regarding 1) How bullying behavior towards ethnic Chinese occurs after the Covid-19 pandemic in Islamic schools, 2) What is the role of Framing Media regarding the Covid 19 pandemic which encourages bullying behavior towards ethnic Chinese in Islamic schools , 3) How does citizenship education prevent bullying of ethnic Chinese after the Covid-19 pandemic in Islamic schools. This research uses qualitative methods to obtain theories and argumentative bases based on the results of literature research from various sources such as magazines, articles and books and related to the problems to be solved. As we know, currently many teenage attitudes are emerging that are contrary to multiculturalism. Among them, bullying behavior often occurs, especially among school children. Bullying is said to be a form of child abuse carried out by peers of the same age against someone (child) who is